Trace fossils and the agronmomic revolution at the Neoproterozoic – Cambrian transition in Southwest Gondwana - Aceñolaza, Guillermo Federico (2009)
The Ediacaran-Early Cambrian transition in the southwestern margin of Gondwana is represented in the Andean Margin of South America by the thick sequence of the Puncoviscana Basin. In southern Africa, the Nama and Vanrhynsdorp groups display partially equivalent successions. Trace fossil assemblages are well known from both regions, with relatively simple, low diversity forms in the lower stratigraphic levels. An increase in complexity is recorded in the upper sector of the Andean and African sequences, with a variety of Treptichnus-type traces that denotes a more gradual diversity increase towards the Cambrian than generally accepted. Trace fossil associations indicate that the fossiliferous levels of the Puncoviscana Basin may predate the uppermost lower Cambrian (pre-trilobite) successions of the Nama and Vanrhynsdorp groups, and lasted into the ‘trilobitic’ Cambrian. Intergradations between Treptichnus and different ichnogenera cast doubts on using related ichnospecies in Ediacaran-Early Cambrian biozonation.